Pelatihan terhadap Pemahaman Materi Konseling Kelompok dengan Pendekatan Realitas pada Guru Bimbingan dan Konseling - Manora, Elsa; Sofah, Rahmi (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2019)
This study aims to determine the effect of group counseling training on the understanding of Guidance and Counseling Teachers. The research method used is an experimental method with a pre-experimental design of One Group Pretest-Posttest Design. The research subjects of this research were guidance and counseling teachers who participated in group counseling training using a reality approach to community service lecturers of guidance and counseling study program. The number is 30 people consisting of 16 guidance and counseling teachers for SMP/MTs, and 14 SMA/SMK in Indralaya Ogan Ilir. Data collection techniques using test techniques. The test wasgiven before treatment and after treatment. The data analysis technique used is the ttest (paired sample T test). The results of the study mean the pretest score is 14.5 and the standard deviation is 4.0, while the average score for the post-test is 17.9 with a standard deviation of 4.3. The results of the t test obtained t count = -6.89. The result of the t-test obtained is 6.89, which is greater than the t-table 2.04 with 0.00 < 0.05 in a significant level of 5%. This shows that there is an effect of training on understanding group counseling materials for guidance and counseling teachers.